Designing textbooks for an indigenous language: The case of Nambya - Mthokozisi Moyo (Pioneer publications, 2023)
This article outlines the steps involved in writing secondary learners’ textbooks from the vantage point of the authors and publishers. It unpacks the technicalities, merits, and demerits of team-authoring of materials in the context of revitalisation of indigenous languages within Zimbabwe’s education system. The main focus is on the technical steps involved in the compilation and design of the textbook series. It evaluates the approaches that were used in the development of the Nambya textbooks in light of informing practice in subsequent future works by the same group or others.